(untitled) (Религиски дијалог и соработка, 2021)
Soka Gakkai developed in Japan in the aftermath of the atomic bombs in Hiroshima and Nagasaki, and few causes are dearest to its members than the campaign for the total elimination of nuclear weapons. The paper reviews the tragedy of Hiroshima and Nagasaki and its consequences in Japan and internationally, noting the problems preventing the United Nations from effectively achieving the aim of nuclear disarmament. In the second part, it details the anti-nuclear activities of Soka Gakkai, starting from the seminal speech of September 8, 1957 in Yokohama by its second president, Josei Toda. It then summarizes the efforts of Soka Gakkai’s third president, Daisaku Ikeda, on behalf of nuclear disarmament, and their results.